Teori dan Psikologi Belajar Terhadap Pembelajaran Sains dalam Meningkatkan Prestasi Belajar di SD Al Amanah Jeneponto - Rafiuddin (Maximal Journal : Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya dan Pendidikan, 2024)
The theory of learning in science learning is the ability children in cognitive learning, a teacher should look for a solution and think about learning and studying psychology. An understanding of psychology and the theories of how students learn and how to apply the theory in the classroom. Experts assess and study the nature of learning in many ways so that it can happen resemblance or similarity between the theory that one with the other theories, are complementary and not closed any possibility of conflicting theories. Because each theory has advantages and weaknesses of their own, the more important thing to note is that the user can appropriately use the advantages of each theory class each. Science learning for children requires an understanding of concepts and the ability to link between the concepts that have been held in cognitive structure, with a constructivist approach teachers are expected to be able to become facilitators for children in an effort to actualize the ability of children who are still buds and further developing what is little or only partially actualized , to the maximum extent possible in accordance with existing conditions